A ratiometric fluorescent probe for the rapid and specific detection of HSO3− in water samples. (26th January 2021) - Mu, Xinyue; Zhu, Jinbiao; Yan, Liqiang; Tang, Ningli
Abstract: Hydrosulphite (HSO3 − ), as a common and important chemical reagent, is widely used in everyday life, however excessive use and abuse of HSO3 − can cause potential harmful effects on the environment and in biological health. In this paper, we describe the design and preparation of a colorimetric and ratiometric fluorescence probe for the visual detection of HSO3 − (excitation wavelengths were, respectively, 336 nm and 520 nm). This method showed some advantages including simple preparation, high selectivity, fast response, and significant colour and fluorescence ratio (F450 /F594 ) changes in the presence of HSO3 − . In addition, this probe was used successfully for the detection of HSO3 − in real water samples and showed a good recovery rate range. Abstract : A ratiometric fluorescent probe for the rapid and specific detection of HSO3 − with a low detection limit and a wide concentration range was developed.